2001
DOI: 10.1128/jcm.39.11.4066-4075.2001
|View full text |Cite
|
Sign up to set email alerts
|

PCR Fingerprinting of Candida albicans Associated with Chronic Hyperplastic Candidosis and Other Oral Conditions

Abstract: The purpose of this study was to genotype strains of Candida albicans to determine whether specific types were associated with chronic hyperplastic candidosis (CHC). A total of 67 candidal isolates from CHC patients (n ‫؍‬ 17) and from patients with other oral conditions (n ‫؍‬ 21) were genotyped by PCR fingerprinting employing two interrepeat primer combinations (1245 and 1246 primers or 1251 primer) and a single minisatellite-specific M13 primer. The most suitable primer for fingerprint analysis was found to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
28
0
3

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 42 publications
1
28
0
3
Order By: Relevance
“…From this viewpoint, the utilization of vitamin A or isotretinoin could be useful for the regulation of epithelial differentiation. Isotretinoin acts on the immune system and also on the mechanisms of inflammation, and is considered to exert a chemopreventive effect against apoptosis and angiogenesis ( [16][17][18][19]. The oral cavity is a wet environment where it is not easy to apply a drug that can remain in contact with lesions for an extended time (20).…”
Section: Discussionmentioning
confidence: 99%
“…From this viewpoint, the utilization of vitamin A or isotretinoin could be useful for the regulation of epithelial differentiation. Isotretinoin acts on the immune system and also on the mechanisms of inflammation, and is considered to exert a chemopreventive effect against apoptosis and angiogenesis ( [16][17][18][19]. The oral cavity is a wet environment where it is not easy to apply a drug that can remain in contact with lesions for an extended time (20).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of C. albicans have shown that the same strain can persist for months to years, but few reports have pointed out that multiple strain types can coexist in individual patients (2,14,29). Among the 25 patients with multiple isolates, 19 patients (76%) contained multiple isolates that exhibited identical or highly related PFGE and MLST genotypes, which may imply that one strain of C. glabrata colonized each patient.…”
Section: Discussionmentioning
confidence: 99%
“…Some surveys of oral isolates have shown the same strain persisting for months to years (4,17). Occasionally, authors have suggested that multiple strain types coexist in samples from some patients (27,69,83), but such findings are in the minority and may reflect technical sensitivities and variabilities in the typing methodologies used in some cases.…”
mentioning
confidence: 97%
“…Most longitudinal and/or multiple-site epidemiological work demonstrating strain maintenance in C. albicans has been done with superficial isolates, particularly with cultures from the oral cavities of human immunodeficiency virus (HIV)-infected patients (2,3,6,19,31,48,51,61,71,72,90,96), with vaginal isolates (1,37,49,64,65,73,76,91), with other sources of superficial isolates (4,17,74,97), or with superficial surveillance cultures from hospitalized patients (60,81,89). Some surveys of oral isolates have shown the same strain persisting for months to years (4,17).…”
mentioning
confidence: 99%